2020
DOI: 10.18632/aging.102970
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of 9-cis retinoic acid reduces beta-amyloid deposition via inhibiting astrocyte-mediated inflammation

Abstract: Alzheimer's disease (AD) is associated with the accumulation and deposition of a beta-amyloid (Αβ) peptide in the brain, resulting in increased neuroinflammation and synaptic dysfunction. Intranasal delivery of targeted drugs to the brain represents a noninvasive pathway that bypasses the blood-brain barrier and minimizes systemic exposure. The aim of this study was to evaluate the therapeutic effect of intranasally delivered 9-cis retinoic acid (RA) on the neuropathology of an AD mouse model. Herein, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Aβ is produced by the cleavage of APP by βand γ-secretase [29]. Previous studies have found that the overexpression of APP led to the increase of Aβ, which is closely related to the occurrence of AD [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. It has been shown that BHBA can improve cognitive behavior in an Alzheimer's disease mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Aβ is produced by the cleavage of APP by βand γ-secretase [29]. Previous studies have found that the overexpression of APP led to the increase of Aβ, which is closely related to the occurrence of AD [30][31][32][33][34][35][36][37][38][39][40][41][42][43]. It has been shown that BHBA can improve cognitive behavior in an Alzheimer's disease mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Cells. Aβ [25][26][27][28][29][30][31][32][33][34][35] (synthesized by Shanghai Sangon Biological Engineering Technology & Services Co.) was diluted in distilled water at a concentration of 16 mmol/L and was maintained at 37°C for 7 days to preage the peptide. N2a cells were divided into four groups: the control (NT) group, the NaB (2 mM) group, the Aβ 25-35 (40 μmol/L) treatment group, and the Aβ 25-35 (40 μmol/L) with NaB (2 mM) pretreatment group.…”
Section: Treatment Of N2amentioning
confidence: 99%
See 3 more Smart Citations